Association of Low-Risk Human Papillomavirus Infection with Male Circumcision in Young Men: Results from a Longitudinal Study Conducted in Orange Farm (South Africa) - Chloé Tarnaud; Pascale Lissouba; Ewalde Cutler; Adrian Puren; Dirk Taljaard; Bertran Auvert (Hindawi Limited, 2011)
Background. Low-Risk Human Papillomavirus (LR-HPV) genotypes 6 and 11 cause genital warts. This study investigated the association of LR-HPV infection with male circumcision (MC). Methods. We used data from the South African MC trial conducted among young men. Urethral swabs, collected among intervention (circumcised) and control (uncircumcised) groups, were analyzed using HPV linear array. Adjusted LR-HPV prevalence rate ratio (aPPR) and Poisson mean ratio (aPMR) of number of LR-HPV genotypes were estimated using log-Poisson regression, controlling for background characteristics, sexual behaviour, and HIV and HSV-2 statuses. Results. Compared to controls, LR-HPV prevalence and mean number of genotypes were significantly lower among the intervention group ((8.5% versus 15.8%; aPRR: 0.54, P<.001) and (0.33 versus 0.18; aPMR: 0.54, P<.001), resp.). Mean number of LR-HPV genotypes increased with number of lifetime sexual partners and decreased with education level and consistent condom use. Conclusions. This study shows a reduction in LR-HPV infection among circumcised men.